A study of morphological patterns of dermatoglyphics among mother and fetus in different ABO, RH blood groups - AL-Kalifa, Nameer Fadhel (Diyala Journal of Medicine, 2018)
Background: Dermatoglyphics, the study of fingerprints are unceasing and characteristic. It has been found useful in forensic medicine and documentation purpose. It is beneficial in medical diagnosis of genetically inherited diseases and in detection of crimes. Objective: To associate between digital dermatoglyphics patterns in ABO, Rh blood groups in the mother and fetus and to assess their significance. Patients and Methods: The pregnant mother and her baby of the 2016 in Al-Batool teaching hospital, designed the study populace. The present study has been carried out on 90 fit individuals (mothers her baby) undergoing medical screening. Fingerprints were attained by Ink method. Parameters studied were arches, whorls, loops. Results: Common of the subjects (42%) in the study were of blood group A followed by blood group O, B and AB of whom (30%) were Rh-positive. The common distribution of pattern of finger print showed high frequency (30%) of loops followed by whorls and arches. Almost similar order was detected in both Rh-positive and Rh negative individuals or A, B, AB and O blood groups, except blood group O- ve which showed more whorls. Conclusion: There is an association between distribution of finger print pattern and blood groups.